Perverse incentives at the banks? Evidence from a natural experiment - Sumit Agarwal; Faye H. Wang (Federal Reserve Bank of Chicago, 2009)
Incentive provision is a central question in modern economic theory. During the run up to the financial crisis, many banks attempted to encourage loan underwriting by giving out incentive packages to loan officers. Using a unique data set on small business loan officer compensation from a major commercial bank, we test the model's predictions that incentive compensation increases loan origination, but may induce the loan officers to book more risky loans. We find that the incentive package amounts to a 47% increase in loan approval rate, and a 24% increase in default rate. Overall, we find that the bank loses money by switching to incentive pay. We further test the effects of incentive pay on other loan characteristics using a multivariate difference-in-difference analysis.
Keywords: D3; G2; J3; 330; Incentive Compensation; Small Business Lending; Loan Officers; Piece Rate and Salaries